ICT Enterprise Architecture uses the Indonesian e-Government Rating Dimension (PeGi) (Case Study of ICT Masterplan of Cirebon City Government) - R. , A. E. Virgana; Hamdani, Dani; M. , Benny Chaniago; Purno, Ari (International Journal of Psychosocial Rehabilitation, 2020)
In accordance with the Instruction of the President of the Republic of Indonesia No. 3 of 2003 concerning National Policy and Strategy for the Development of e-Government, each government agency must have a Strategic Plan for e-Government Development. The Cirebon City Government plans that the master plan for the development of information and communication technology is the basis for the development of information technology applications and infrastructure in the Cirebon City Government. This study uses the Indonesian e-government rating dimension, the guidelines of which are made by the Ministry of Communication and Information of the Republic of Indonesia. Five dimensions have been determined that will be studied by the ICT masterplan, namely policy, institution, infrastructure, applications, and planning. It is expected that a plan for the implementation of information technology (e-government) in the Cirebon City government is in line with the latest developments and needs and the availability of guidelines in the development, maintenance, and management of information technology in order to support the tasks and functions of the Cirebon City administration.